PROGNOSTIC IMPACT OF LACTATE DEHYDROGENASE IN LOW AND HIGH-RISK MYELODYSPLASTIC SYNDROMES: A SINGLE CENTER EXPERIENCE FROM PAKISTAN - Kumar, Vijeet; Majeed, Laraib; Arshad, Aisha; Fatima, Naveena; Anwar, Nida (Journal of Ayub Medical College Abbottabad, 2025)
Background: The higher level of serum lactate dehydrogenase (LDH) is linked to a worse prognosis in myelodysplastic syndromes. Therefore, the present study was planned to investigate the prognostic utility of baseline lactate dehydrogenase (LDH) in predicting survival of low and high-risk myelodysplastic syndrome (MDS) patients. Methods: This cross-sectional study was conducted at National Institute of Blood Diseases and Bone Marrow Transplantation (NIBD-BMT), PECHS campus, Karachi, Pakistan from January 2022 to January 2024.A total of 44 newly diagnosed MDS patients were included. The Complete Blood counts (CBC) were analyzed by using Sysmex XN-1000 (Sysmex Corporation, Kobe, Japan). The IPSS was calculated for risk stratification. Serum LDH levels were done by using Cobas c311 (Roche Diagnostics, Germany). Baseline LDH <220IU/l was considered normal. All parameters were analyzed by using SPSS version 23. Results: In a total of 44 de novo MDS patients, 29 (65.9%) were male. The median age was 54 ranging 7‒87 years. Among the patients, 32 (72.7%) had LDH ≥220IU/l. No significant differences were found between LDH levels and International Prognostic Scoring System (IPSS) risk stratified groups (p=0.311). Significant association of LDH levels was found with cytogenetic risk category (p=0.011). The median survival time for individuals with LDH ≥220 IU/l was 18 months (95% CI: 8.86‒27.14), compared to 19 months (95% CI: 10.97‒27.03) for LDH < 220IU/l (p=0.296). Conclusion: The present study did not identify significant association between LDH levels and MDS classification, risk stratification, or survival outcomes. Our findings underscore the importance of further research to elucidate the role of LDH in MDS prognosis.